Notes d'un paleògraf a propòsit del matritensis 9.750 de la Biblioteca Nacional («Curial e Güelfa») - Gimeno Blay, Francisco M. (Caplletra. Revista Internacional de Filologia, 2015)
The thesis of Jaume Riera i Sans (1991), pretending that the text of the novel Curial e Giielfa contained in this ms. of Madrid's national Library was a modern forgery, kindled a lively controversy. After a thorough study of the handwriting, with special reference to the capital letters, Prof. Gimeno's reaches the conclusion that without the slighest possible doubt this ms. was written during the xvth century.